Cultivating Environmental Culture in Islamic Elementary School: Menumbuhkan Budaya Lingkungan di Sekolah Dasar Islam - Mastoni Muhajirin; Mufarrihul Hazin; Amrozi Khamidi; Mochamad Nursalim (Academia Open, 2025)
Background: Environmental awareness does not emerge spontaneously; it must be instilled early through sustainable education. Specific Background: In Indonesia, the Adiwiyata School Program is a national strategy to embed environmental values within education, yet its integration in Islamic-based schools remains underexplored. Knowledge Gap: Previous research mainly focused on public schools and technical practices without examining how policy models and religious values interact in private Islamic schools. Aim: This study analyzed the implementation of environmental education policy in SDIT Permata Mojokerto using Edward III’s model of policy implementation while considering social, economic, political, and religious contexts. Results: Findings revealed that effective communication, sufficient resources, positive teacher and student attitudes, and structured bureaucracy, supported by favorable socio-political conditions, fostered a sustainable environmental culture. Programs such as Waste Donation, Clean Friday, and thematic learning linked to Qur’anic verses strengthened the integration of Islamic values. Novelty: The research demonstrates how religious values can legitimize and reinforce environmental education policy, expanding theoretical discourse beyond secular frameworks. Implications: The study suggests that policy implementation in faith-based schools can serve as a model for contextualizing environmental education, ensuring sustainability while preserving religious identity. Highlight Integration of environmental policy with Islamic values shaped school culture. Effective communication and resources sustained environmental practices. Socio-economic independence and community support reinforced implementation. Keywords Environmental Education, Islamic School, Policy Implementation, School Culture, Adiwiyata